2017
DOI: 10.1136/bcr-2017-219441
|View full text |Cite
|
Sign up to set email alerts
|

‘All that glitters is not gold’: when hyperammonaemia is not from hepatic aetiology

Abstract: Hyperammonaemia is often caused by decompensated liver disease. However, non-hepatic causes can sometimes result in hyperammonaemia, severe enough to cause symptoms.We report a case of a 65-year-old man with a history of hypertension and bilateral peripelvic renal cyst who presented with acute confusion. Laboratory investigations revealed hyperammonaemia and normal liver function test. The abdominal ultrasound did not reveal any finding of liver disease or portal-systemic shunting but demonstrated bilateral pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…Our results are consistent with previous studies, in which an increase in ammonia was associated with higher rates of infection by Enterobacteriaceae [ 3 , 13 , 22 ]. Therefore, serum ammonia should be measured when risk factors are present, such as intestinal infection or infection by E. coli .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with previous studies, in which an increase in ammonia was associated with higher rates of infection by Enterobacteriaceae [ 3 , 13 , 22 ]. Therefore, serum ammonia should be measured when risk factors are present, such as intestinal infection or infection by E. coli .…”
Section: Discussionsupporting
confidence: 93%
“…An interesting finding in our study is that non-hepatic hyperammonemia may be associated with an increased risk of SAE [ 12 ]. SAE is mainly characterized by symptoms of delirium with changes in a patient’s consciousness, and it also can lead to coma [ 13 ]. Our study demonstrated that patients with hyperammonemia had lower GCS scores.…”
Section: Discussionmentioning
confidence: 99%
“…It may also happen with normal hepatic function when mitochondrial pathways are interrupted by Reye's syndrome or medications, such as valproic acid, carbamazepine, salicylate, topiramate, or cytotoxic agents . Additionally, renal tubular acidosis, urinary tract dilatation or urinary tract infection, pregnancy, and hypoglycin may contribute to nonhepatic hyperammonemia.…”
Section: Discussionmentioning
confidence: 99%